Simple chemical bath deposited zinc oxide nanoflowers and their applications for extended-gate FET pH sensor / A. B. Rosli …[et al.] - Rosli, Aimi Bazilah; Ismail, Ahmad Syakirin; Awang, Zaiki; Abdul Khalid, Muhammad Farid; Shariffudin, Shafinaz Sobihana; Herman, Sukreen Hana (Universiti Teknologi MARA, 2019)
Zinc Oxide (ZnO) nanostructures deposited using simple chemical bath deposition (CBD) at different deposition time ranging from 1 to 4 hours on indium tin oxide (ITO) substrates are proposed as sensing membrane of extended-gate field effect transistor (EGFET) pH sensor. The ZnO nanostructures were grown without any seed or catalyst layer. The deposited samples were characterized on their physical properties in order to investigate the correlation between physical properties and pH sensing behavior based on the influence of various deposition time to the physical properties. It is evident from the FESEM result that the nanostructures growth density is directly proportional to the growth time. Same goes on crystallinity quality of the samples that shows the same pattern as growth density. The physical properties of the ZnO nanostructures can be related to the immersion time and in turn influence the pH sensor performance. All deposited samples showed the ability to be applied as the sensing material for the EGFET pH sensor with the highest performance was obtained from the 3-hours sample having sensitivity of 56.0 mV/pH and 0.9997 linearity. The high sensitivity obtained from the 3-hour sample is related to high growth density of ZnO nanostructures that provide high surface area which facilities more contact between sensing membrane and pH buffer for ion adsorptions.